Congenital soft tissue stenosis of the external auditory canal with canal cholesteatoma: Case report and literature review. (July 2020) - Windsor, Alanna M.; Ruiz, Ryan; O'Reilly, Robert C.
Abstract: Congenital external auditory canal stenosis (EACS) is a spectrum of abnormalities affecting the external and middle ear. We report a 6 year-old patient with EACS affecting the lateral fibrocartilaginous canal that was successfully repaired. This patient highlights a variant of EACS characterized by lateral soft tissue narrowing with normal osseous development. Most previous studies of CAA have described severe forms associated with complete atresia, bony stenosis, and middle ear malformations. Stenosis affecting only the fibrocartilaginous canal is a milder form resulting from premature arrest of the canalization process during embryologic development, and may predispose to cholesteatoma formation.